2010
DOI: 10.1063/1.3437085
|View full text |Cite
|
Sign up to set email alerts
|

Defect-enhanced ferromagnetism in Gd- and Si-coimplanted GaN

Abstract: GaN grown by metal-organic chemical vapor deposition was coimplanted with Gd+ ions with energy of 155 keV and dose of 2.75×1010 cm−2 and Si4+ ions with energies of 5 and 40 keV and corresponding doses of 8×1011 and 3.6×1012 cm−2. The implanted samples were not annealed before characterization. X-ray diffraction measurements revealed that the implanted GaN exhibited no secondary phase formation or clustering effects attributable to Gd. Superconducting quantum interference device magnetometer measurements indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…The role of defects was also pointed out in experiments with Gd-implanted GaN and as-grown GaN:Gd epitaxial layers. 11,14,22 The dependence of the effective saturation magnetization per Gd atom m Gd,eff on the Gd concentration c Gd is depicted in Fig. 2 and compares well with values in the literature.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…The role of defects was also pointed out in experiments with Gd-implanted GaN and as-grown GaN:Gd epitaxial layers. 11,14,22 The dependence of the effective saturation magnetization per Gd atom m Gd,eff on the Gd concentration c Gd is depicted in Fig. 2 and compares well with values in the literature.…”
supporting
confidence: 68%
“…11 Nearly all recent reports about Gd-doped GaN show a strong ferromagnetic signal at room temperature. [8][9][10][12][13][14] Only few exceptions show partly ferromagnetic samples or no ferromagnetism. 15,16 The origin of the ferromagnetic order in GaN:Gd is still unknown.…”
mentioning
confidence: 99%
“…inducing intrinsic longrange magnetic order were also investigated in III-V nitrides such as GaN and AlN. Davies et al' work suggested that gallium vacancies play an important role in ferromagnetic ordering in Gd-and Si-coimplanted GaN [34]. Wu et al reported that Al vacancy in Mg-doped AlN lead to spin-polarized ground states [9].…”
Section: Magnetic Property Analysismentioning
confidence: 96%
“…According to previous reports and the above XRD patterns, the ion implantation process also creates a profusion of point defects such as vacancies and interstitials into the host material. These defects can also have magnetic moment [17]. From the above discussion, we know that ferromagnetism in Sm-doped GaN is due to Sm 3?…”
Section: Magneto-optical Analysismentioning
confidence: 96%